The Influence of Endorser in Social Media Toward Consumer Decision Making with AISAS Model (Attention, Interest, Search, Action, and Share - Meitia Rini; Nuddin Harahab (Faculty of Fisheries and Marine Science, Brawijaya University, 2018)
This research discusses about the influence of endorser or brand ambassador in social media (Facebook, Twitter and Instagram) toward consumer decisions making as a part of Integrated Marketing Communication (IMC) analyse with AISAS model (Attention, Interest, Search, Action and Share) as the impact of the endorser usage. This research was conducted quantitatively with examining the endorser independent variables in social media into AISAS model as its dependent variable. In this research explained that AISAS model is the development of AIDA model (Attention, Interest, Desire and Action) which has been widely used on advertising in social media and other media, then developed into AISAS model in appropriate with the internet era and the character of modern consumers who tend to searching before making a purchase for the product. From this research found that the endorser usage or brand ambassador on Fiesta Seafood product advertisement in social media has positive effect on attention, interest, search, action and share of consumer. By combining advertising activities in social media and other media, is expected can assist Fiesta Seafood become a leader market in Indonesia processed seafood products.